Uji Keandalan Penguraian Data Hujan Penguraian (Disagregasi) Untuk Pemodelan Hidrograf Banjir Di Das Kelapa Sawit - Hidayah, Entin (Fakultas Teknik, Universitas Brawijaya, 2012)
Abstract: This study explores accuracy of short term rainfall disaggregation model by modeling rainfall runoff. Storm hydrographs show rapid responses to rainfall with a short time to peak. The spatial rainfall disaggregation process used multivariate daily rainfall (MuDRain) model on 4 manual rainfall rain gauges (MRR) and 3 automatic rainfall rain gauges (ARR) used as reference the hydrographs were satisfactorily modeled using the Hydrologic Engineering Centre–Hydrologic Modeling System (HEC-HMS). Parameter calibrations were done on case 1 that rainfall runoff modeling used the rainfall data from 7 rain gauges (MRR and ARR). Model validation (case 2) used the rainfall data from 3 rain gauges (ARR). The efficiency indexes of (case 1) and (case 2) are 0.97 and 0.74, respectively. Based on these preliminary findings, it could be suggested that rainfall disaggregation would be able to serve reasonably well in regulating basic hydrological functions.Key words: rainfall, runoff, disaggregation, MuDRain